Therapeutic effects of Azadirachta indica A.Juss. leaves in malaria-induced male Wistar rats - Ngozi K. Achi; Chimaraoke Onyeabo; Daniel A. Nnate; Chima A. Ekeleme-Egedigwe; Igwe K. Kalu; Ikedichim C. Chibundu; Grace C. Wokoma (GarVal Editorial Ltda., 2018)
Context: Azadirachta indica has long been used in herbal or folk medicine as a remedy for the treatment of malaria and the administration of herbal preparations has raised concerns on their toxicity. Aims: To determine the phytochemical content of A. indica and its therapeutic effect on indices of clinical importance in malaria-induced male Wistar rats. Methods: Plant material was extracted with ethanol, and the lethal dose (LD50) on the rats was determined before the study. Normal and Plasmodium berghei infected rats were divided into eight groups of five rats each with groups 1 and 2 serving as normal and disease control respectively. Lumartem was administered twice daily at oral therapeutic doses of artemether/lumefantrine (2/12 mg/kg) and plant extract at 300 and 500 mg/kg body weight. After 5 days of treatment, all the animals were sacrificed according to their groups for the experimental analysis. Results: The plant extract was considered safe with LD50 > 5000 mg/kg body weight. Quantitative phytochemical studies showed a high concentration of alkaloids, tannin, and terpenoids. Treatment with both extracts of A. indica and lumartem in malaria-infected rats showed a slight reduction in triglycerides while total cholesterol, HDL, and LDL levels increased significantly (p < 0.05). Increase in body weight of rats treated with A. indica was dependent on the concentration of extract administered. Treatment of malaria with the extract and lumartem resulted in a slight restoration of the hematological values. Conclusions: This study shows that both Azadirachta indica and lumartem was practically safe and well tolerated.